2020
DOI: 10.1016/j.fertnstert.2020.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and oncologic outcomes after fertility-sparing surgery for early stage cervical cancer: a systematic review

Abstract: This review sought to evaluate the current literature on reproductive and oncologic outcomes after fertility-sparing surgery for early stage cervical cancer (stage IA1-IB1) including cold-knife conization/simple trachelectomy, vaginal radical trachelectomy, abdominal radical trachelectomy, and laparoscopic radical trachelectomy with or without robotic assistance. A systematic review using the preferred reporting items for systematic reviews and meta-analysis (PRISMA) checklist to evaluate the current literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 100 publications
3
74
1
1
Order By: Relevance
“…In cases of major deviations, SLN assessment was completed according to the protocol at the central laboratory, without the need of additional sample transportation back to the referring sites. Patients scheduled for fertility-sparing surgery were eligible in the trial since they could profit from intraoperative triage the most [27][28][29]. The threshold for upper tumor size in fertility-sparing treatment was 2 cm, which corresponds to the recent international recommendations [9].…”
Section: Discussionmentioning
confidence: 99%
“…In cases of major deviations, SLN assessment was completed according to the protocol at the central laboratory, without the need of additional sample transportation back to the referring sites. Patients scheduled for fertility-sparing surgery were eligible in the trial since they could profit from intraoperative triage the most [27][28][29]. The threshold for upper tumor size in fertility-sparing treatment was 2 cm, which corresponds to the recent international recommendations [9].…”
Section: Discussionmentioning
confidence: 99%
“…The MIS approach is associated with lower intraoperative and postoperative morbidity [106,109]. Fertility outcomes with open or MIS (most of the included studies were of laparoscopic surgery) have been reported to be lower than with vaginal trachelectomy [105,110]. In contrast, a large series from an experienced robotics centre has shown a high fertility rate of 81% following robotic radical trachelectomy, associated with a low rate of preterm deliveries.…”
Section: Fertility-sparing Treatmentmentioning
confidence: 99%
“…A systematic review by Nezhat et al [110] reviewed the current evidence on reproductive and oncological outcomes after fertility-sparing surgery for stage 1A1e1B1 cervical cancer, including cold-knife conisation/simple trachelectomy, vaginal, open and minimally invasive radical trachelectomy with or without robotic assistance. In total, there were 65 studies, encompassing 3044 patients who underwent fertility-sparing surgery, including 1047 pregnancies.…”
Section: Fertility-sparing Treatmentmentioning
confidence: 99%
“…The risk of recurrence is increased with tumors >2 cm. 2,3 Further contraindications include a history of sterility and age >40-45 years. A laparoscopic nodal staging should be performed primarily, and patients with nodal infiltration need to be managed on an individual basis.…”
Section: Oncological Considerationsmentioning
confidence: 99%
“…In a recent meta-analysis that investigated FSS (all types) for early-stage cervical cancer, 3044 patients including 1047 pregnancies were identified. 2 The pregnancy rate of women trying to conceive was 55%. The highest pregnancy rate was found in patients undergoing VRT (67.5%).…”
Section: Obstetrical Considerationsmentioning
confidence: 99%